Corporate Social Responsibility and Socio-Environmental Conflicts in Peruvian Mining Company - PÉREZ FALCÓN, Julián; RAMIREZ ASIS, Edwin; VIZCARRA ARANA, Jesús; ESPINOZA MUÑOZ, Einer; RAZA, Mohsin (Journal of Environmental Management and Tourism, 2022)
Corporate social responsibility is an extremely important aspect that every organization should give the proper importance; on the other hand, socio-environmental conflicts should be considered by every company to have an optimal development, which is why the present study proposes the relationship between these two aspects. The objective of this research study was to determine the relationship between corporate social responsibility of the mining company Lincuna S.A. and the socio-environmental conflicts of the inhabitants of the province of Ticapampa, Ancash Region, Peru. The present study is a non-experimental, descriptive correlational study where the statistically determined sample was 332 subjects who answered a questionnaire of 30 questions, 15 about corporate social responsibility and 15 about socio-environmental conflicts.